Underlying mechanism for high-temperature superconductivity in ternary hydride AB_{2}H_{24} - Bowen Jiang; Xin Zhong; Hanyu Liu (Physical Review Research)
Recent studies have highlighted the potential for achieving room-temperature superconductivity in the clathrate hydride prototype AB_{2}H_{24} with the P6/mmm space group symmetry. To investigate the underlying superconducting mechanism for this class of frameworks, we performed comprehensive first-principles calculations by systematically substituting metal elements from groups I to IV of the periodic table. The results identify 21 dynamically stable compounds at 300 GPa, exhibiting an extraordinary variation in superconducting critical temperatures (T_{c}), ranging from 276 K in AcSc_{2}H_{24} to 2 K in ThCe_{2}H_{24}. Through detailed structural analysis, we proposed two key model parameters, S_{couple} and coupling strength (CS), to elucidate the strong correlation with superconducting properties (showing correlation coefficients of 0.87 and 0.93 with respect to T_{c}). These model parameters are further demonstrated to be extendable for other clathrate-type hydrides, such as Li_{2}MH_{16/17} and binary superhydrides MH_{6}, MH_{9} and MH_{10}. The proposed CS shows strong predictive capability, achieving an overall correlation coefficient of 0.85 across different clathrate hydride systems. These findings provide insights into the fundamental mechanisms governing the superconducting properties of clathrate hydrides, offering useful guidance for future superconductor design.